Pengaruh Latihan Metode Drill Terhadap Kemampuan Akurasi Passing Bola Permainan Futsal Pada Siswa Ekstrakulikuler SMPN 1 BEBER - Mochamad Yarobi (STKIP Muhammadiyah Kuningan, 2023)
Mochamad Yarobi (NIM 182223074), The Effect of Drill Method Training on theAccuracy Ability of Passing Futsal Balls in Extracurricular Students of SMPN 1BEBER. Physical Education, Health and Recreation Study Program. The purposeof this study was to determine the effect of drill method training on the ability ofball passing accuracy in futsal games for extracurricular students of SMPN 1BEBER. This study uses experimental research methods. The population andsample in this study were extracurricular students of SMPN 1 BEBER with asample of 12 people. The research instrument used in this study was a passing testwith a distance of 15 meters from the goal. The results of the analysis andprocessing of preetest data obtained the lowest passing 3, the highest passing 7,while the posttest data results obtained the lowest passing 5, the highest passing 9in 10 trials using the right foot 5 times and the left foot 5 times. This shows anincrease in the passing ability of extracurricular students of SMPN 1 BEBER.Based on the test, it shows that the two tests have a normal distribution.Therefore, to test the hypothesis using the independent samples t-test, the pre-testand post-test values showed a Sig p value of 0.730 > 0.05 in the Equality ofMeans section of 0.000, because the Sig value < 0.005, it can be concluded thatthere is a significant effect on the ability of passing accuracy using the drillmethod on extracurricular students of SMPN 1 BEBER.Keywords: Passing accuracy and drill method